The Impact of Surveillance on Journalist Activism (Forum Ilmu Sosial, 2020)
This study explored how alleged surveillance by the authorities was presented, responded to, and impacted journalists' activism. Employing the Panopticon framework, it is expected that those who become the object of surveillance change their behavior to become more submissive to authority. By means of a series of in-depth interviews with two print media journalists and one media researcher, it was found that journalists were threatened by the â€œdisturbanceâ€ that befell them. However, this would not change them in conveying the public interest. They also adapted to the threats that came about. Many interview subjects refused to participate in this study because of the sensitivity and potential risks they received from the discussion.